Iranduba: ribeirinhos na travessia produzida: análise de um projeto para populações rurais no Estado do Amazonas - Chaves, Maria do Céu Câmara (1990)
This dissertation has as its central focus the analysis of the 'exclusion-integration' process to which' the riverine populati~n in the State of Amazonas is submitted, trying to recognize their field of autonomy as a basic mechanism for their reproduction, namely, how they experience and respond to concrete forms of subordination to which they are submitted. The work was developed in the Mid-Amazon Region in the municipality of Iranduba where a State interventíon through the creation of a 'Núcleo de Colonização Dirigida' (Guided Colonization Nucleus) in high lands and the implantation of the 'Cidade Hortigranjeira de Iranduba ' (Horticultural City of Iranduba) project, in 1976, took place. This intervention is here treated as 'Travessia dos Ribeirinhos' (Crossing of the riverine people)